Transforming Education: Optimizing Learning Environments through the Fusion of Signal Processing and IoT - Grandhi, Harsha (AG Volumes, 2024)
The education sector is not an exception to the widespread use of "Internet of Things (IoT)" applications. The Internet of Things' ability to create smart cities provides a workable answer to the difficult problems of cost-effectiveness, sustainable development, and energy management in light of growing urban populations and environmental demands. Along with privacy and security of data issues in Internet of Things installations, the study also discusses the ethical and legal implications of data collection. Future developments and opportunities for IoT use in education are also covered by the study, including the blending of artificial intelligence and machine learning. The results demonstrate notable decreases in energy use, financial savings, and noteworthy contributions to the eradication of greenhouse gas emissions, ultimately leading to an increase in environmental sustainability.